Developmentand Psychometric Evaluation of Persian version of the Quick Speech in Noise Test in Persian Speaking 18-25 Years Old Normal Adults - Abdollah Moossavi; Mohanna Javanbakht; Hamideh Arbab Sarjoo; Enayatollah Bakhshi; Behrooz Mahmoodi Bakhtiari; Yoones Lotf (Shiraz University of Medical Sciences, 2016)
Background: One of the common problems of those who refer to audiology clinics, is difficulty of hearing in noisy conditions. Different tests have been developed for diagnosis and quantification of reduced ability of speech perception in noise and the Quick Speech-in-Noise test is one of the most appropriate of them. The goal of the present study was to develop and validate the Persian version of the Quick Speech-in-Noise Test in normal, Persian speaking, 18-25 year-old participants. Methods: This study had two main stages: first, developing the test materials and determining the content validity and the second, determining the equivalency of the test material lists, and assessing the reliability of them. In the first stage, sentences having content validity were developed and recorded. In the second stage,in order to determine list equivalency, the lists were presented to 60 Persian-speaking (gender balanced), 18-25 year-old students and the average SNR-50 for each list was calculated using the Spearman-Kärber formula. In order to determine the reliability of the test, the test was again administered to15of the primary participants, two weeks later. Results: among80 sentences developed, 60 received enough credits from audiologists and speech therapists. Average SNR-50 in the Persian language was calculated as -0.25 dB. Thirty six content valid sentences, according to special criteria, were divided into six lists each containing 6sentences. The SNR-50 for each list revealed that lists number 2,3, 4and 5 were equivalent. Examination of test-retest reliability indicated that lists number 1,2,3,4 and 6 were reliable (P<0.05). Conclusion: Present study was developing three equivalent and reliable lists (number 2,3,4) for the Persian version of the Q-SIN test which are useful for diagnosing and selecting the best rehabilitation method for people with reduced speech perception in noise.